Scale-dependent climatic drivers of human epidemics in ancient China - Tian, Huidong; Yan, Chuan; Xu, Lei; Büntgen, Ulf; Stenseth, Nils C; Zhang, Zhibin (Proceedings of the National Academy of Sciences of the United States of America, 2017)
A wide range of climate change-induced effects have been implicated in the prevalence of infectious diseases. Disentangling causes and consequences, however, remains particularly challenging at historical time scales, for which the quality and quantity of most of the available natural proxy archives and written documentary sources often decline. Here, we reconstruct the spatiotemporal occurrence patterns of human epidemics for large parts of China and most of the last two millennia. Cold and dry climate conditions indirectly increased the prevalence of epidemics through the influences of locusts and famines. Our results further reveal that low-frequency, long-term temperature trends mainly contributed to negative associations with epidemics, while positive associations of epidemics with droughts, floods, locusts, and famines mainly coincided with both higher and lower frequency temperature variations. Nevertheless, unstable relationships between human epidemics and temperature changes were observed on relatively smaller time scales. Our study suggests that an intertwined, direct, and indirect array of biological, ecological, and societal responses to different aspects of past climatic changes strongly depended on the frequency domain and study period chosen.
Keywords: epidemics; Communicable Diseases; Climate Change; scale dependent; epidemie; Prevalence; klimatické změny; China; History, Medieval; natural disaster; lidé; infekční nemoci; disease; climate; prevalence; dějiny středověku; dějiny starověku; Epidemics; Disasters; Čína; katastrofy; History, Ancient; Humans